2020
DOI: 10.1016/j.eja.2019.125960
|View full text |Cite
|
Sign up to set email alerts
|

Future development of apricot blossom blight under climate change in Southern France

Abstract: Climate change will have several consequences for agro-systems, one of which will concern changes to the development of pathogens. Because of the losses it causes, particularly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Such misalignment of previsions is less effective than it might appear, because the above mentioned findings are mainly due to predicted trends in the temperate regions of Europe, where increased temperatures will match the optimal requirement of the considered pathogens (Chaloner et al, 2021). In accordance with our results, Bregaglio et al (2013) found that climate warming might determine a lower disease incidence for those regions where temperature will exceed optimal ones with respect to the pathogen and Tresson et al (2020) identified a reduced blossom blight risk for those cultivars that will be exposed to future drier and warmer conditions. Our findings also show that the timing of occurrence of favorable environmental conditions for brown rot spreading, i.e.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such misalignment of previsions is less effective than it might appear, because the above mentioned findings are mainly due to predicted trends in the temperate regions of Europe, where increased temperatures will match the optimal requirement of the considered pathogens (Chaloner et al, 2021). In accordance with our results, Bregaglio et al (2013) found that climate warming might determine a lower disease incidence for those regions where temperature will exceed optimal ones with respect to the pathogen and Tresson et al (2020) identified a reduced blossom blight risk for those cultivars that will be exposed to future drier and warmer conditions. Our findings also show that the timing of occurrence of favorable environmental conditions for brown rot spreading, i.e.…”
Section: Discussionsupporting
confidence: 89%
“…In the present work, we fed our mechanistic model with two climate-related inputs, that are daily average air temperature and a Boolean variable (presence/absence) of daily precipitation occurrence. We chose these two weather variables because their combined effect had already been related to the Monilinia incidence risk (Tresson et al, 2020) and showed to promisingly grasp the core dynamics of the system without the need of using further, more refined climate variables. Also, making reference to variables that can be easily measured, our model results to be easily extendable and applicable to contexts where the availability of climate measurements is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in plant phenology also influence the organisms that depend on them in terrestrial ecosystems and, vice versa, the gaps between the phenology of plants and their pollinators have repercussions on crop productivity [21]. Moreover, changes in the timing of plant development sequences can expose plants not only to climatic accidents but also to diseases [22] and pest attacks [23]. In addition, one of the main strategies of sustainable agriculture is the efficient management of cultural practices, which can be accomplished by the use of well-adapted species and cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Van de Wouw et al ., 2021), varietal precocity (e.g. Tresson et al ., 2020) and the timing of the release of natural enemies to regulate pest populations (e.g. Nicot et al ., 2019; O'Sullivan, Belt & Thatcher, 2021).…”
Section: The Drivers Of the Phenology Of Plant Pathogenic Fungimentioning
confidence: 99%